Engaging Stakeholders, Students, Faculty and Librarians to Improve the Reading List Service at SMU Libraries: a Lean Case Study - Red-Elaurza, Cristina; Usah, Jennifer (2017)
A current trend in Libraries is to use Lean to improve processes and services while doing more with less. The SMU Libraries has been on a Lean journey since 2013, partnering with the Office of Business Improvement to train Library staff in the use of Lean Six Sigma to improve productivity and service levels. Recently, the SMU Libraries and the Office of Business Improvement collaborated with students enrolled in the Managing Process Improvement course to review one of the key services provided to students and faculty. The team applied the Lean Six Sigma methodology to the Reading List service, looking closely at the persistent link and scanned chapter workflows. The goal of the project was to reduce the lead time for the Reading List service. This paper presents a case study to illustrate the application of Lean Six Sigma tools in identifying and investigating the root causes of the problem, analysing the process metrics, prioritising potential solutions, running experiments and creating a control plan to sustain the improvements. Based on the information given by SMU Libraries and faculty members, the students suggested some alternatives to improve the processes and conducted experiments to test their recommendations. The project quickly resulted in better engagement between the Libraries, faculty and students and showed early indications of faster turnaround time by faculty, enabling the Libraries to provide better service to both faculty and students.